Madura Foot: A Rare Case of Eumycetoma and Proposed Classification and Treatment Guidelines - Kow, Ren Yi; Goh, Kian Liang; Sabbir Husain, Aziz; Hamdan, Asmah Hanim; Low, Chooi Leng (IIUM Medical Journal Malaysia, 2022)
Madura foot or mycetoma pedis is a chronic granulomatous disease of the foot caused by fungus or gram-positive aerobic bacteria. It is commonly encountered in tropical and subtropical countries but is rare in Malaysia. We reported a 40-year-old Rohingya refugee who has been resident in Malaysia for the past 11 years presented with a long-standing left foot mass that was proven to be a eumycetoma. A wide local excision of the mass and full-thickness skin graft were done, followed by a course of 6-month postoperative itraconazole. He subsequently recovered well without sequela. A high index of suspicion should be raised in a patient presenting with a chronic mass and discharging sinus in order to diagnose and treat mycetoma as early initiation of therapy leads to better outcomes. Based on literature review, we propose a new classification of eumycetoma and its treatment guideline.